PENGARUH KONTEN REVIEW BEAUTY INFLUENCER TERHADAP MINAT BELI PRODUK SKINCARE: STUDI PADA PENGIKUT AKUN TIKTOK @TASYAFARASYA - Medo Maulianza; Nur Asni Gani; Celline Octavia (Taksasila Edukasi Insani, 2026)
The development of TikTok as a digital marketing communication medium has encouraged the increasing role of beauty influencers in influencing consumer behavior, especially in the skincare industry. This study aims to analyze the influence of beauty influencer review content on TikTok on the purchase interest of skincare products among followers of the @tasyafarasya account. The study used a quantitative approach with an explanatory survey method. The study population was 3,440,000 followers of the @tasyafarasya account, while a sample of 100 respondents was determined using the Slovin formula with a simple random sampling technique. Data collection was carried out through a Likert-scale questionnaire, then analyzed using simple linear regression with the help of IBM SPSS Statistics 26. The results showed that beauty influencer review content was in the high category with an index value of 73.17, while purchase interest obtained an index value of 73.95. The regression analysis showed that beauty influencer review content had a positive and significant effect on purchase interest of skincare products (β = 0.244; p 0.001), with a coefficient of determination of 46.2%. These findings indicate that informative, credible, and engaging review content contributes to increasing consumer purchase intention. This research reinforces the Uses and Effects Theory, which suggests that exposure to digital media can lead to changes in consumer behavior in the context of marketing communications.Keywords: beauty influencer, TikTok, review content, purchase intention, skincare, Uses and Effects Theory.